ANALISIS TINGKAT KEPUASAN PEMBELAJARAN BAHASA ARAB KURIKULUM MERDEKA BAGI SISWA KELAS XI MAN 2 PONOROGO TAHUN AKADEMIK 2023-2034 - Suryadarma, Yoke; Kurniawan, Edo; Doni, Rahmad; Al Farabi, Fahmy Akhyar (Proceedings of International Conference on Islamic Civilization and Humanities, 1970)
The study conducted aimed to evaluate the satisfaction level of grade XI students at MAN 2 Ponorogo regarding Arabic language learning using the independent curriculum. The research focused on three indicators of satisfaction: assurance, empathy, and tangibles. The data collection method employed was quantitative-descriptive, which involved distributing questionnaires via Google Forms. The results of the descriptive analysis indicated that the majority of students expressed high satisfaction with Arabic language learning using the independent curriculum, with a value of 63.3%. The quality of teaching and infrastructure were the two factors that contributed the most to overall satisfaction. Based on the literature, other indicators of learning satisfaction such as reliability and responsibility were not specifically considered in this study. Overall, the findings suggest that the independent curriculum implemented for Arabic language learning in grade XI at MAN 2 Ponorogo is generally meeting the students' satisfaction levels.